A formação do professor que ensina matemática nos anos iniciais do ensino fundamental para o uso das tecnologias digitais da informação e comunicação - Almeida, Josiane Marques Duarte (2023)
The advent of Digital Communication and Information Technologies (DICT) has changed the way we relate to knowledge and teaching with a focus on the development of competencies linked to the use of DICT has returned to academic discussion, with the National Common Curriculum Base (BNCC), which reinforces the importance of continuing training for teachers who teach mathematics in the initial years of basic education. Thus, the object of this research is the relationship between continuing education processes and the development of digital competences for more meaningful mathematics teaching, with the following question as a starting point: how has the relationship between the use of TDIC in mathematics teaching been constituted, from the perspective of teachers who teach mathematics in the early years of elementary school in the municipal education network of Fortaleza? Thus, our general objective is to analyze the perceptions of the teachers taking part in the "Teacher researcher: theory and practice" training and extension course on the use of DICTs in the teaching of mathematics in the early years of elementary school. This course, linked to the research group Weaving Cognitive Networks of Learning (G-TERCOA/CNPq/UFC), was the locus of the research, and the subjects were six participating teachers. The data presented and analyzed here refers to discussion forum five, which addressed the topic of modeling and the use of TDIC in mathematics teaching. Data was collected during participation and interaction in the forum and from questionnaires on prior and final knowledge, as well as participant observation during the online meetings. The research is characterized as basic, exploratory and took place in three phases: 1- bibliographical research; 2- empirical research; and 3- writing the dissertation. The work is qualitative in nature and the data was analyzed using content analysis, in accordance with the assumptions of Moraes (1999). We relied theoretically on the studies by Aguerrondo and Vaillant (2015), Vaillant (2020), the reports and studies launched by the Innovation Center for Brazilian Education (2022) and Papert (2008) to support our discussions about digital competences, ICT associated with mathematics teaching and teacher training, among other aspects. The results of this research show that, despite the transformations that our way of learning and teaching has undergone as a result of the insertion of DICTs into our daily lives, the frequency with which teachers use them as a teaching tool is still low. This is because teachers are still lagging behind when it comes to developing the digital skills needed to use platforms such as the TelEduc Multimedia Virtual Learning Environment (VLE), adopted as the official platform for the G-TERCOA/CNPq/UFC continuing teacher training courses. The conclusion is that there is still a considerable way to go before ICT can be effectively used in math teaching. For this to happen, it will be essential to implement effective continuing training for teachers in order to enable them to develop the skills needed to use ICT.